PENERAPAN SUPERVISI AKADEMIK SEBAGAI UPAYA UNTUK MENINGKATKAN KINERJA GURU SEKOLAH DASAR - Samudi Samudi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This study aims to improve the performance of teachers who are considered still lacking. For that done aninnovation by applying academic supervision. This research is a school action research, which carried out twocycles with four stages: planning, implementation, observation, and reflection. The results of this study indicatethat the application of academic supervision can improve the performance of elementary school teachers. This isevidenced by the results of research: In the planning indicators in the first cycle to get a score of 60.00 increasedin cycle II with a score of 75.00%. In the implementation of learning indicators obtained a score of 55.00%increased in cycle II with a score of 70.00%. And on learning scoring indicator get score 55,00% increase withscore 70,00%. In addition, the average teacher performance also increased in the first cycle of teacherperformance average is 56.66 with enough category, in the second cycle increased to 71.67 with Good category.